1978
DOI: 10.1111/j.1469-7998.1978.tb03344.x
|View full text |Cite
|
Sign up to set email alerts
|

Some adaptations between Danaus plexippus and its food plant, with notes on Danaus chrysippus and Euploea core (Insecta: Lepidoptera)

Abstract: Behaviour of the egg‐laying Monarch in captivity suggests that the concentration and quality of cardiac glycosides in the food plant are not important oviposition cues. The presence of eggs (as previously noted by Urquhart, 1960) and larvae feeding on the food plant, act as mild deterrents. The butterfly's emetic potency (see Table XIII(a)) can sometimes surpass that of the leaves of the host plant itself. Unidentified factors, providing the internal plant environment, are more important as cardiac glycoside s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

1981
1981
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(15 citation statements)
references
References 28 publications
2
12
1
Order By: Relevance
“…It is well established that cardenolides protect monarch butterflies from bird attacks [21] and both monarch and queen butterflies, are mimicry models for the viceroy (Limenitis archippus) [27,28] underlining the effectiveness of cardenolide sequestration as a defence. Moreover, it was shown that across milkweed butterfly species (D. plexippus, the plain tiger, D. chrysippus and E. core) emetic potency acting on predators is linked to the amount of cardenolides stored [29]. Our study thus suggests a mechanism of how the third trophic level can engage in plant-insect coevolution by favouring altered tolerance and use of toxins by herbivores.…”
Section: Introductionmentioning
confidence: 68%
“…It is well established that cardenolides protect monarch butterflies from bird attacks [21] and both monarch and queen butterflies, are mimicry models for the viceroy (Limenitis archippus) [27,28] underlining the effectiveness of cardenolide sequestration as a defence. Moreover, it was shown that across milkweed butterfly species (D. plexippus, the plain tiger, D. chrysippus and E. core) emetic potency acting on predators is linked to the amount of cardenolides stored [29]. Our study thus suggests a mechanism of how the third trophic level can engage in plant-insect coevolution by favouring altered tolerance and use of toxins by herbivores.…”
Section: Introductionmentioning
confidence: 68%
“…Brower (I 969) using this and other pieces of information suggested that female D. plexippus cue in on secondary plant substances, particularly cardiac glycosides and oviposit preferentially on those plants containing large amounts of these compounds. Dixon et al (1978), on the other hand, reported that butterflies consistently selected (except for one aberrant case) plants with the lowest concentration of cardiac glycosides of those plants offered. Their preference in descending order was A .…”
Section: Discussionmentioning
confidence: 95%
“…The latter two species have been placed into the genus Gomphocarpus by some authors (e.g. Smithers, 1973;Dixon et al, 1978) however Everist (1974) retains them in the genus Ascelpias and we follow his nomenclature. Experimental design was dictated by availability of plants and butterflies and hence some comparisons were not possible.…”
Section: Methodsmentioning
confidence: 99%
“…This is further complicated by the fact that many milkweed herbivores sequester cardenolides. For example, Dixon et al. (1978) wrote in passing that fifth instar monarchs sometimes drink latex from plant wounds.…”
Section: Introductionmentioning
confidence: 99%
“…This is further complicated by the fact that many milkweed herbivores sequester cardenolides. For example, Dixon et al (1978) wrote in passing that fifth instar monarchs sometimes drink latex from plant wounds. One of us (Agrawal) has also observed larvae imbibing latex, but this has only been while very carefully notching a leaf ( Figure 1B), presumably to depressurize the leaf.…”
Section: Introductionmentioning
confidence: 99%